Characteristic CT angiography findings and clinical value of catheter-related central venous thrombosis in hemodialysis patients with end-stage renal disease. (June 2023) - Chen, Yushu; Li, Wanjiang; Bai, Hongli; Zhang, Yiteng; Lu, Chunyan
Background: Central catheter-related thrombosis (CRT) is the most common catheter-related complication in patients with end-stage renal disease (ESRD) but is often underappreciated and misdiagnosed by radiologist. Purpose: To find the computed tomography angiography (CTA) characteristics of central CRT, then raise the diagnosis of this disorder. Material and Methods: A total of 301 eligible patients with ESRD who experienced both chest multi-phase multidetector CTA (MDCTA) and digital subtraction angiography were enrolled in the final analysis. The location, shape, and related signs of the central CRT in MDCTA images were evaluated. Independent-samples T test, chi-square test, and binary logistic regression were analyzed using SPSS software. Results: In total, 166 patients were found to have CRT using MDCTA, and this was verified by DSA. Central CRT was usually irregular in the superior vena cava segment, and the angle of the contact area between central CRT and catheter was <180° (all P  < 0.05). Age, collateral circulation, and venous stenosis were shown to have significant differences when compared to patients without CRT (all P  < 0.05), but there were no significant differences about the sex or catheter insertion site. In addition, age and collateral circulation were the factors found to be significantly associated with thrombosis ( P  < 0.05). In particular, the thrombosis was 2.213 times more likely to be found in those patients with collateral circulation (odds ratio = 2.213, 95% confidence interval = 1.236–3.961). Conclusion: Chest multi-phase MDCTA can effectively reduce the missed diagnosis and misdiagnosis of central CRT. It is worth paying more attention to the central CRT especially when the collateral circulation is observed.